(untitled) (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2025)
The doctrine of soul transmigration has appeared in the mythological ancient pagan religions whereas obtained variety of thoughts according to the difference of the incubator environments. Before long ,this belief has transferred to some other religions and philosophies. So, Judaism has adopted this cult after submitting it to some adjustment to fit in with its thoughts and faith . but, there wasn’t a total acceptance about the origin of this doctrine among their holly books according to historical reasons from one hand, on the other hand, the matter of soul still under studying and researching till now and it is fully subtle , there is no global and general vision of acceptance about it. All attempts which had aimed to revel its truth, had run to many difficulties because it is one of the unperceivable and unrevealed by itself .in addition to be overwhelm the human mind which lead its destiny to be more difficult to be a wave of . thus, many endeavors had occurred to solve this matter and as a result to that effort , the messianic redemption has been appeared into Jewish kabbalah , the redemption count on doing the prayers day and night , also offering oblations to the holy spirit.